Exploring the Local Language Students’ Foreign Language Anxiety in EFL Online Class: Students’ Genders and Speaking Performance - Lukman Hakim (Universitas Pendidikan Indonesia, 2022)
Students’ anxiety, speaking performance and their relation to genders have been investigated extensively in the EFL context and most participants are English students, but most of the studies with the same variables were conducted in an offline setting. Thus, the purpose of this research is to describe the anxiety levels of students who studied another language than English in learning English and to investigate the relationship between their anxiety and performance in English-speaking classes. By employing a quantitative approach, 32 male and 66 female Sundanese Language and Culture Study Program students whose anxiety levels were assessed using Horwitz et al.’s (1986) Foreign Language Classroom Anxiety Scale (FLCAS) participated voluntarily in the research. Because the data were normally distributed and homogenous, the obtained data were analyzed using parametric statistical tools; independent t-test and Pearson Product Moment Correlation. The results imply that the majority of the participants’ anxiety levels were moderate, and there was no statistical difference in students’ anxiety levels between male and female students. Further exploration of the relationship between the anxiety levels of the students and their speaking performance was weak and negative (r = -0.12, p .68). Thus, the online and offline foreign language classroom settings do not seem to differentiate students’ anxiety levels for both male and female students.